DAMPAK TEKNOLOGI DIGITAL TERHADAP KEHIDUPAN SOSIAL, EKONOMI, DAN ETIKA MASYARAKAT - Sakilah; Romlah; Riniyati; Nurrohmah; Purkon Nasution; Anjar Sulistyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has brought fundamental changes to various aspects of society, particularly in social, economic, and ethical dimensions. The emergence of the internet, artificial intelligence, social media, and other digital platforms has accelerated the flow of information, improved work efficiency, and created new opportunities in education and the economy. However, these advancements have also generated serious challenges, including the digital divide, violations of privacy, data security threats, the spread of misinformation, and excessive dependence on technology. This study aims to analyze the impact of digital technology on social, economic, and ethical aspects of society through a library research approach by reviewing relevant scholarly literature. The findings indicate that digital technology provides significant benefits for societal development, yet it requires careful management to minimize its negative consequences. Therefore, collaboration among governments, academics, and society is essential to ensure the responsible and sustainable use of digital technology. Keywords: digital technology, society, social impact, digital ethics;